2021
DOI: 10.1111/pbi.13680
|View full text |Cite
|
Sign up to set email alerts
|

High‐quality evergreen azalea genome reveals tandem duplication‐facilitated low‐altitude adaptability and floral scent evolution

Abstract: Summary Azalea belongs to Rhododendron, which is one of the largest genera of flowering plants and is well known for the diversity and beauty in its more than 1000 woody species. Rhododendron contains two distinct groups: the most high‐altitude and a few low‐altitude species; however, the former group is difficult to be domesticated for urban landscaping, and their evolution and adaptation are little known. Rhododendron ovatum has broad adaptation in low‐altitude regions but possesses evergreen characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 99 publications
2
46
0
Order By: Relevance
“…In the present study, the analyses of enzymes involved in terpenoid biosynthesis pathways suggest that the expansion of the TPS family, primarily through tandem gene duplications, may have led to the terpenoid diversity in W. villosa . It has been reported that the catalytic production of TPS is related to the sequence similarity (Karunanithi et al., 2020; Wang et al., 2021); in general, WvTPSs in the same tandem gene cluster tend to have closer evolutionary relationships and more similar catalytic products. For example, WvTPS35 and WvTPS37 from tandem gene cluster 10 were found to have similar catalytic products (Figure 5a; Figure S14).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the analyses of enzymes involved in terpenoid biosynthesis pathways suggest that the expansion of the TPS family, primarily through tandem gene duplications, may have led to the terpenoid diversity in W. villosa . It has been reported that the catalytic production of TPS is related to the sequence similarity (Karunanithi et al., 2020; Wang et al., 2021); in general, WvTPSs in the same tandem gene cluster tend to have closer evolutionary relationships and more similar catalytic products. For example, WvTPS35 and WvTPS37 from tandem gene cluster 10 were found to have similar catalytic products (Figure 5a; Figure S14).…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale RNA interference experiments in C. elegans [ 81 , 82 ] and D. melanogaster [ 83 ] revealed that about 65% and 85% of the genes are dispensable in these two species, respectively; when the loss of a gene causes pathway dysfunction, the organism will choose alternative pathways to ensure the stable performance of the pathway function [ 84 ]. The most direct manifestation of “gene gain” events is the increase in the number of genes, which can help individuals adapt to the environment in which they survive [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified several genome characteristics that possibly contributed to the adaptation of V. darrowii to subtropical climates. Tandem duplicates contribute to gene family expansions and allow alternative transcriptional regulation, and thus have been considered a common strategy for adaptive evolution to altered environments 123,124 . A clear functional bias in the tandemly duplicated genes has been observed in plants, making tandem genes good index for environmental adaptation 123,125,126 .…”
Section: Discussionmentioning
confidence: 99%